Observations on the water quality management of larval and postlarval rearing tanks of Penaeus monodon hatchery at Cox's Bazar, Bangladesh - Das, N G; Sarwar, S M M; Parvez, M M (Indian Journal of Fisheries, 2011)
The present study was carried out in the Pioneer Hatchery Ltd. situated atCox's Bazar sea coast of southeastern apex of Bangladesh. Water parameterssuch as temperature, salinity, dissolved oxygen, pH etc. greatly influence thelarval and Jlostlarval development and their survival rate in the rearing tanksof Penaeus monodon hatchery. For quality assessment water samples werecollected fimr times daily from the larval and postlarval rearing tanks andmeasured the water temperature, salinity, DO, pH, H2S, NH3-N, N02-N, N03-N, P04-P, Si02• The results of analysis of these parameters have been criticallyevaluated to find out their optimal range in the hatchery management ofPenaeus monodon.